2018
DOI: 10.21608/ejbo.2018.4698.1194
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Thermophilic Soil-Isolated Paenibacillus sp. NBR10 as a Chitinolytic and Biocontrol Bacterium-In vitro Study

Abstract: A mONG microbial enzymes, chitinases received increased attentions due to their wide applications especially in agriculture sector for biocontrol of fungal phytopathogens. The growing interest in chitinases with thermostability nature, forced many researchers to isolate and characterize novel chitinase producing-bacteriafrom extreme environments. The present study describe characterization of thermostable chitinase produced by thermophilic soilisolated bacterial strain NBR10 from Rafha governorate, Saudi Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Enzymes are proteins in nature, inactivates above 50°C, denatures at 70°C, and are unable to provide sufficient activation energy at very lower temperatures (El-Sayed et al, 2019). In this study, the optimum temperature for the purified enzyme was observed at 30°C, which was earlier reported as 37°C by (El-Sayed et al, 2019); after attaining optimum temperature, chitinase activity gradually decreases from 40°C to 70°C (Figure 4c). The stability of chitinase was found in the range of 30°C to 60°C (Figure 4d).…”
Section: Effect Of Temperature On Enzyme Stability and Activitysupporting
confidence: 59%
“…Enzymes are proteins in nature, inactivates above 50°C, denatures at 70°C, and are unable to provide sufficient activation energy at very lower temperatures (El-Sayed et al, 2019). In this study, the optimum temperature for the purified enzyme was observed at 30°C, which was earlier reported as 37°C by (El-Sayed et al, 2019); after attaining optimum temperature, chitinase activity gradually decreases from 40°C to 70°C (Figure 4c). The stability of chitinase was found in the range of 30°C to 60°C (Figure 4d).…”
Section: Effect Of Temperature On Enzyme Stability and Activitysupporting
confidence: 59%